SISTEM PENDUKUNG KEPUTUSAN DALAM MENENTUKAN ACCEPTABLE QUALITY LEVEL (AQL) PADA SARUNG TANGAN RUBBER LATEX DENGAN METODE MULTI FACTOR EVALUATION PROCESS DI PT. SHAMROCK MANUFACTURING CORPORA - Nuraisana Nuraisana (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2018)
Shamrock Manufacturing Corpora is one of the companies engaged in manufacturing. To produce good and satisfying goods is one of the important factors that become the company's principle. How to get good results in a product must be good in quality management. In the matter of quality management, the Acceptable Quality level value is very important in determining the feasibility of an item, so a Decision Support System is used with the Multi Factor Evaluation Process Method. The settlement method used in this study is the Multi Factor Evaluation Process. This method is implemented into the Visual Basic 2008 programming language, then the calculation is done by multiplying the weights with the value of the product criteria. After the multiplication results are obtained, each criteria will be totaled. With this system, the AQL Decision Support System program results can help provide AQL values quickly and accurately at PT. Shamrock Manufacturing Corpora.